A general fractal model of Internet traffic - Molnar, S.; Terdik, G. (Proceedings LCN 2001. 26th Annual IEEE Conference on Local Computer Networks, 2001)
The fractal nature of Internet traffic has been observed by several measurements and statistical studies. A new monofractal stochastic process called Limit of the Integrated Superposition of Diffusion processes with Linear differential Generator (LISDLG) is presented, which effectively characterizes network traffic monofractality. Several properties of the LISDLG model are presented including the covariance structure, cumulants, spectrum and bispectrum. The model captures high-order statistics by means of the cumulants. The relevance and validation of the proposed model are demonstrated by application studies for measured Internet traffic.